A benchmark assessment of ecosystem health indicator species groups at Bali Barat National Park. Issue 1 (March 2020) - Winarni, N L; Dwiyahreni, A A; Hartiningtias, D; Sunaryo; Supriatna, J
Abstract: Bali Barat National Park was assessed for its suitability to receive RFS Protected Area Credits TM . Part of the requirement is to select indicator groups from among 5 terrestrial taxa, within the eligible forest in the park boundaries, (1) insects - butterflies, (2) amphibian, (3) reptiles, (4) birds, and (5) mammals that can serve as r indicators for the overall ecosystem health of the TNBB. To select indicator groups, a biodiversity survey was conducted for during August-September 2015 in 3 study sites within Bali Barat National Park, Lebak Buah, Megatransect, and Brumbun. Different taxa were surveyed using peer-reviewed methods. The best indicator species within each taxa group (plants, butterflies, herpetofauna, birds and mammals) were defined based on their abundance and distribution in the eligible forest of the project area using Indicator Value method. Potential animal and plant indicator species were then assessed empirically for their cost-effectiveness based on survey effort and cost during the initial survey. Then they were evaluated for generality, functional importance, available scientific knowledge, and cross-taxon representation. Our results suggested that birds would be the best indicator species group, followed by butterflies, and plants. Such indicator is important surrogate for ecosystem health which can be used for conservation management priorities within protected area.